Towards reimbursement of mobile digital health applications? An international comparison of practices. (30th September 2020) - Degelsegger-Márquez, A; Panteli, D
Abstract: Background: The hitherto largely unregulated market of mobile digital health applications is undergoing significant changes, particularly concerning the growing segment of apps that aim at integrating care processes or replacing traditional forms of diagnosis or therapy. The inclusion in the benefit basket of statutory health systems is of relevance when exploring viable business models for app developers. Description of the problem: So far, countries largely limit coverage to apps developed by authorities within the statutory health system, or provide guidance for payers in the form of app lists or quality assessment criteria. However, there are new regulatory efforts aiming to promote innovation for mobile digital health applications by creating pathways to general reimbursement, as exemplified by the 2019 German Digital Healthcare Act. Results: Our contribution illustrates how evidence-based reimbursement decisions can be configured for mobile digital health applications. We will compare frameworks from different contexts, including the new German regulation, the UK's NHS App Store and the Evidence Standards Framework for Digital Health by NICE as well as the work of the French National Health Authority (Haute Autorité de Santé). Building on case studies, we will provide a typology of practices, which covers elements spanning consumer guidance to assessment approaches to full reimbursement decision-making. Conclusions: Based on the proposed typology, we will discuss challenges and opportunities of reimbursement systems for mobile health apps from a public health perspective and seek to refine the typology by incorporating input from session participants and profiting from the global nature of the conference.